Utilization Of Modified Waste Staghorn Coral As A Base Catalyst In Biodiesel Production - Zul, Nabilah Atiqah (2019)
ABSTRACT This work focuses on producing a novel catalyst to synthesize methyl esters from triglycerides by the reaction with methanol. Firstly, calcium oxide derived from staghorn coral was characterized and applied in the transesterification process of refined, bleached and deodorized, (RBD) palm olein. The reaction only yielded about 62.1 ± 4.3 % methyl esters. Therefore, a catalyst modification was carried out by impregnating the staghorn coral with potassium hydroxide, KOH as an effort to further enhance its catalytic effect. The modified catalyst (K-CSC) was then used as a base catalyst in the methanolysis of RBD palm olein and waste cooking oil. For RBD palm olein transesterification, the best reaction conditions to obtain methyl esters content of 94.8 ± 0.5 % was found to be 4 wt.% catalyst, 4 h reaction time, and 15:1 methanol to oil molar ratio. Besides that, K-CSC catalyst also successfully transesterified waste cooking oil at the reaction conditions of 4 wt.% catalyst, 5 h reaction time and 18:1 methanol to oil molar ratio and produced 89.5 ± 4.8 % biodiesel. The reusability of K-CSC catalyst was also studied and unfortunately,